Mathematics achievement emotions of high school students in Kazakhstan - Gur, Tamer; Balta, Nuri; Dauletkulova, Aigul; Assanbayeva, Gulzhaukhar; Fernández-Cézar, Raquel (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Emotions such as anxiety, fear, and frustration can interfere with cognitive processing and hinder our ability to learn and perform well on tasks. Mathematics is a school subject that could generate various emotions in students. This study examined mathematics achievement emotions of students across gender, grade level, and academic performance. Data was collected from 246 students using a questionnaire measuring seven emotions: enjoyment, pride, anger, anxiety, shame, hopelessness, and boredom. Results indicated that except for females’ higher pride, we did not find differences between males' and females’ emotions. Ninth-grade students demonstrated higher anxiety and shame than grade seven and eight students. Finally, students’ mathematics exam grades are weakly correlated with all seven measured emotions. Our findings add to the literature by presenting that emotions are contextual. Except for pride, the results clearly indicated that math emotions in our sample are gender irrelevant and further imply that the socio-cultural context of Kazakhstan supports females to compete with their male friends.